Differential learning assisted with SANTUY mobile application for improving students’ mathematical understanding and ability - Rohaeti, Euis Eti; Evans, Brian R.; Wiyatno, Toyo; Prahmana, Rully Charitas Indra; Hidayat, Wahyu (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Equations are often used in mathematics and other subjects, which means that a media can teach students how to solve equations, particularly linear equations of two variables, or Sistem Persamaan Linear Dua Variabel (SPLDV) as it is called in Indonesian, is needed. However, most teachers are still focused on developing the learning process and teaching materials rather than developing an application technology-based learning media. As we know that technology-based learning is currently the focus of teaching and learning activities in the digital era, especially learning after the pandemic. This study aimed to develop an application that can be a reference for teaching media in learning activities to improve students’ mathematical understanding and ability. The developed application is named, Integrated and Convenient Android-based Simulation or Simulasi Android Terpadu dan Nyaman, abbreviated as SANTUY. This development study with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, explained in detail in the paper, took seventy-five subjects consisting of six expert validators, nine users, and sixty students. The expert validators comprised three media experts and three material experts. The evaluation stage involved students from two groups, each consisting of thirty students. The results showed that the average percentage of the feasibility of the SANTUY SPLDV solution simulation-assisted application with differential learning nuance was 79.62%, which means the application is adequate. The level of usefulness of the SANTUY SPLDV solution simulation-assisted application with differential learning nuance was 86.11%, which is categorized as “excellent”. In addition, using the SANTUY SPLDV application had a direct positive influence on improving students’ mathematical understanding and ability.